COUNTER-RADICALIZATION IN EARLY CHILDHOOD THROUGH EFFECTIVE COMMUNICATION BETWEEN EDUCATION STAKEHOLDERS IN BIMA - Akhmad Asyari; Kadri Kadri (Universitas Islam Negeri (UIN) Mataram, 2020)
This research reveals the reality of early childhood education in Bima, West Nusa Tenggara as an area prone to radicalism, especially to see the policies and implementation of the counter-radicalization agenda in early childhood, including portraits of communication between stakeholders in tackling the spread of radicalism in Bima. This qualitative research took place from August 2018 to July 2019. The results showed that early childhood education institutions in Bima had not maximally used counter-radicalization content as teaching material even though they lived in the areas prone to radicalism. Communication between education stakeholders such as parents, educators, and the government has also not been effective. This is reflected in the lack of collective counter-radicalization action, so that preventive steps to counter radicalism seem minimal. The lack of coordination and communication for education against radicalization counter-narratives at the early childhood level has made hopes for an inclusive generation in Bima to be born.